2013
DOI: 10.1093/mnras/stt1279
|View full text |Cite
|
Sign up to set email alerts
|

Superbubble breakout and galactic winds from disc galaxies

Abstract: We study the conditions for disk galaxies to produce superbubbles that can break out of the disk and produce a galactic wind. We argue that the threshold surface density of supernovae rate for seeding a wind depends on the ability of superbubble energetics to compensate for radiative cooling. We first adapt Kompaneets formalism for expanding bubbles in a stratified medium to the case of continuous energy injection and include the effects of radiative cooling in the shell. With the help of hydrodynamic simulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…Using Salpeter IMF, and considering stellar masses in the range of 1-100 M , the corresponding surface density of SFR becomes ∼ 0.1 M yr −1 kpc −2 , consistent with observations. Roy et al (2013) has worked out the dynamics of superbubbles triggered by multiple SNe in a disk galaxy, first analytically and then with hydrodynamic simulations, and they found that this simple estimate is supported by detailed calculations. Furthermore, they studied the clumping and fragmentation of the superbubbles during its evolution, and found that thermal instability plays an important role in clumping of the shell material, and in subsequent seeding of Rayleigh-Taylor instability.…”
Section: Threshold Condition For Supernovae Driven Outflowsmentioning
confidence: 97%
See 2 more Smart Citations
“…Using Salpeter IMF, and considering stellar masses in the range of 1-100 M , the corresponding surface density of SFR becomes ∼ 0.1 M yr −1 kpc −2 , consistent with observations. Roy et al (2013) has worked out the dynamics of superbubbles triggered by multiple SNe in a disk galaxy, first analytically and then with hydrodynamic simulations, and they found that this simple estimate is supported by detailed calculations. Furthermore, they studied the clumping and fragmentation of the superbubbles during its evolution, and found that thermal instability plays an important role in clumping of the shell material, and in subsequent seeding of Rayleigh-Taylor instability.…”
Section: Threshold Condition For Supernovae Driven Outflowsmentioning
confidence: 97%
“…Recently, it has been argued that these threshold conditions can be understood from the requirement of multiple SNe driven superbubbles to compensate against radiative loss and be able to break out of the disk with sufficient Mach number in order for the hot interior gas to reach a considerable height above the disk (Roy et al 2013). The basic argument can be illustrated with the help of a simple estimate.…”
Section: Threshold Condition For Supernovae Driven Outflowsmentioning
confidence: 99%
See 1 more Smart Citation
“…2006), a second order accurate Eulerian hydrodynamics code. We carry out 2-D axisymmetric simulations of the following governing equations (see also Roy et al 2013),…”
Section: Numerical Setupmentioning
confidence: 99%
“…At t ∼ 2-3t d , after the superbubble breaks out from the disk, the shell begins to fragment due to radiative cooling and Rayleigh-Taylor instability (RTI; Roy et al 2013). These clumps give rise to the zigzag nature of the angular dependence of the escape fraction.…”
Section: Angular Dependencementioning
confidence: 99%